Detox Handbook - Harper, Jennifer; Edited by Gianni, Margherita (London Dorling Kindersley, 2002)
Containing everything you need to know about detoxing from how to rejuvenate your body, clearing your mind and reclaiming your life, this guide offers three levels of detox from a supportive gentle programe for beginners to a deep purification of body, mind and spirit.
Include Glossary, Index,Bibliography and Acknowledgments
Keywords: Detoxification (Health) -- Rejuvenation -- Fasting